2023
DOI: 10.3390/plants12102048
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification, Expression and Stress Analysis of the GRAS Gene Family in Phoebe bournei

Abstract: GRAS genes are important transcriptional regulators in plants that govern plant growth and development through enhancing plant hormones, biosynthesis, and signaling pathways. Drought and other abiotic factors may influence the defenses and growth of Phoebe bournei, which is a superb timber source for the construction industry and building exquisite furniture. Although genome-wide identification of the GRAS gene family has been completed in many species, that of most woody plants, particularly P. bournei, has n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…With the exception of EgrGRAS51 , all 18 EgrGRAS genes showed significant differences in expression after low-temperature stress treatment compared with normal conditions. The work showed that the expression level of PbGRAS14 in Phoebe bournei increased significantly under low temperature stress [ 44 ]. Huang et al also found that SlGRAS1 , SlGRAS3 and SlGRAS4 in tomato can actively respond to low temperature stress, indicating that these genes were widely involved in low temperature resistance [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of EgrGRAS51 , all 18 EgrGRAS genes showed significant differences in expression after low-temperature stress treatment compared with normal conditions. The work showed that the expression level of PbGRAS14 in Phoebe bournei increased significantly under low temperature stress [ 44 ]. Huang et al also found that SlGRAS1 , SlGRAS3 and SlGRAS4 in tomato can actively respond to low temperature stress, indicating that these genes were widely involved in low temperature resistance [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…To examine how the PbbZIP gene responds to abiotic stressors like temperature, salt, and drought, ve genes in Table 2 (PbZIP32, PbZIP14, PbZIP26, PbZIP67, and PbZIP69) selected from ve representative PbZIP genes based on selection done by (Chang et al 2023;Ziyuan et al). The ve PbZIP genes originate from four distinct subfamilies, each re ecting the subfamily's reaction to abiotic stress.…”
Section: Examination Of Pbbzip Genes Expression Patten Under Various ...mentioning
confidence: 99%
“…To investigate the response of the PbPIN gene family to abiotic stresses such as drought, salt, and temperature stresses, we focused on five genes (PbPIN1, PbPIN7, PbPIN8, PbPIN9, and PbPIN11) that contained a higher number of elements associated with adversity in their cis-acting elements [22,47]. These five genes were considered to be representative of four different sub-families.…”
Section: The Expression Profile Of Pbpin Genes Under Abiotic Stressmentioning
confidence: 99%